Ethical issues in establishing the efficacy and safety of long-acting injectable pre-exposure prophylaxis for HIV prevention: the HPTN 083 trial. Issue 11 (November 2021) - Sugarman, Jeremy; Donnell, Deborah J; Hanscom, Brett; McCauley, Marybeth; Grinsztejn, Beatriz; Landovitz, Raphael J
Summary: Two multinational clinical trials have shown safety and efficacy of long-acting injectable cabotegravir for HIV pre-exposure prophylaxis (PrEP). These results will alter the landscape of HIV prevention and related research. Nevertheless, designing and conducting this research involved several ethical issues. This Viewpoint describes how we managed ethical issues over the duration of one of these trials (HPTN 083). Specifically, we discuss the rationale for pursuing a long-acting injectable agent in the presence of effective oral PrEP, trial design choices, site selection and local standards of prevention, data monitoring and early stopping, effects of the COVID-19 pandemic, post-trial access, and assessment of long-term safety.